The Bau Nyale Tradition of the Sasak Tribe on the Island of Lombok Reviewed from the Rules of Isti'maalu An-Naas Hujjatun Yajibu Al-'Amalu Bihaa - Uswatun Hasanah; Fajar Nurfigiantoro; Anta Mu’min Badji; Marwiyah (Demak Universal Journal of Islam and Sharia, 2024)
The purpose of this study is to analyze the Bau Nyale tradition among the Sasak Tribe people on the island of Lombok from the perspective of the fiqhiyah principle "Isti'maalu An-Naas Hujjatun Yajibu Al-'Amalu Bihaa". Bau Nyale, which means "catching sea worms", is an annual tradition containing spiritual, social, and economic values important to the Sasak community. The research method uses a qualitative-descriptive approach with a literature review. Primary sources are data or information obtained directly from the research object in the form of documentation, notes, or written reports from the Bau Nyale event. Secondary sources are data or information that has been collected and published by others in the form of books and scientific articles that discuss traditions relevant to this tradition and Islamic sharia. The results of the study show that several aspects of the Bau Nyale tradition can be considered following sharia principles, such as togetherness and gratitude. However, there are also elements of mystical beliefs that need clarification and adjustment so as not to contradict the teachings of Islam. The role of scholars and religious leaders is very important in providing guidance and views on the adjustment of this tradition.